Role of Talented Student Office in Encouraging Medical Science Students for Participating in Scientific Olympiads - Leila Vahedi; Morteza Ghojazadeh; Saber Azami Aghdash; Narmin Rasouli; Hakimeh Hazrati (Tabriz University of Medical Sciences, 2015)
Introduction: Scientific Olympiads and the Talented Student Office (TSO) are two strategies for the identification and training of gifted and talented medical science students. The aim of the present study is to identify students' viewpoints about the facilities and privileges of the TSO in stimulating them to participate in the Medical Science Olympiad. Methods: This study was a cross-sectional descriptive study and all participating in the 4th and 5 National Medical Science Olympiad in Iran from 2011 to 21012 were selected using the census method. The validity of a researcher-made questionnaire was confirmed by experts. The content validity index (CVI) was 0.95. Reliability was evaluated using Cronbach's alpha (a=0.8) and the test-retest method (ICC=0.85). Descriptive statistics including frequency, percent, mean and standard deviation were calculated by SPSS 19. Results: In total, 261 students responded to the questionnaires. About 36% of participants in this study had low or very low familiarity with regulations of the TSO. Continuing education to higher levels (master's, Ph.D., residency) and being recruited as a faculty member were the most motivational factors for participation and the least was the permission to select more courses (up to 27 units). Conclusion: Continuing education to higher levels and recruitment as a faculty member were two important factors for participating in the National Medical Science Olympiad. Therefore, personnel in the TSO and related managers should prompt medical students to these centers by highlighting the facilities.